Studi Perbandingan Proses Bisnis Dengan Hasil Implementasi Sistem (Studi Kasus: KB & TK Permata Iman) - Firnanda Iftitah Dewi Antono; Satrio Agung Wicaksono; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
KB & TK Permata Iman has several main business processes, one of them is evaluation of semester learning. Business process analysis result has been described in the Business Process Model and Notation (BPMN) diagram and the execution time of each task is estimated using simulation. The result of business process analysis can give business process recommendation in order to improve efficiency in evaluation of semester learning process. The estimated time of the task has a weakness, that generated time has the possibility of nonconformity with the actual condition. Hence the need for a test to be able to see how accurate the time from the result of business process recommendation with the test time on the implementation results. It needs a system implementation to be able to implement existing tasks on business process recommendation. The system is built using waterfall method with object-oriented approach. The built system is tested to the user to see how much time takes the user to access the system. The result of the user's time test is compared with the estimated time of the task.